2019
DOI: 10.1016/j.heliyon.2019.e01703
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and radiation shielding properties of polyimide/Bi2O3 composites

Abstract: Radiation shielding composites based on polyimide and Bi 2 O 3 were synthesized. Surface and physical-mechanical properties of polyimide/Bi 2 O 3 composites were studied. Bi 2 O 3 particles were modified by polymethylphenylsiloxane for the uniform distribution of filler in composites. This paper presents data on the production of composites in two ways: hot- and cold-pressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…Bi 2 O 3 is a direct bandgap semiconductor. A characteristic feature of Bi 2 O 3 consists of its polymorphism: five modifications, known as α-, β-, γ-, δ-, and ω-Bi 2 O3, were outlined 26 . This refractory high-Z material has a melting point of 817 °C and available in powder form 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Bi 2 O 3 is a direct bandgap semiconductor. A characteristic feature of Bi 2 O 3 consists of its polymorphism: five modifications, known as α-, β-, γ-, δ-, and ω-Bi 2 O3, were outlined 26 . This refractory high-Z material has a melting point of 817 °C and available in powder form 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Different types of polymers need to be separated from each other from the collected plastics waste to get better quality of recycled plastic. Several techniques can be used to separate mixed plastic wastes based on their physicochemical properties such as gravity separation, contact charging, hydro-cyclones and centrifuges, and froth flotation (Pascoe 2003 ). The produced recycled plastic can be used to manufacture new products such as automobile parts, floor carpets, flower vases, park benches, picnic tables, waste paper baskets, crates, plastic lumber, wood–plastic composites which will provide an additional market for recycled plastics.…”
Section: Polymer Composites For Gamma-radiation Shieldingmentioning
confidence: 99%
“…By blending epoxy resin with different weight percent of tungsten powder, tungsten/epoxy composites were prepared and investigated by using two different activities of Co-60 source showing that with the increment of tungsten loading, the shielding property of composites increased (Chang et al 2015). Besides, ethylene-vinyl acetate (EVA)-tungsten composite (Yurt Lambrecht et al 2016) and polyimide/ bismuth oxide (Pavlenko et al 2019) composites revealed high radiation-protective characteristics. The shielding effect and the protective properties of the samples of aluminum alloys with a protective coating were evaluated revealing that tungsten-aluminum oxide (W-Al 2 O 3 ) and tungsten-boron nitride (W-BN) coatings contribute significantly to the attenuation of ionizing radiation fluxes (Vilkov et al 2017).…”
Section: Advances In Polymer Composites By the Use Of Nanofillersmentioning
confidence: 99%
“…It ultimately produces less secondary radiation. Many investigations related to the introduction of micro and nano-sized Bi2O3 powders, as environmentally friendly radiopacifiers in the field of polymer [21][22], glass systems [23][24][25][26] as well as dental cement [27][28][29] technology have been conducted.…”
Section: Introductionmentioning
confidence: 99%